On opposite sides - Schield, Cat (Texas Cattleman's Club: ranchers and rivals, 2022)
"From the moment he sees her, Nolan Thurston wants to know Chelsea Grandin. He tells himself it's just to gain valuable intel in his family's battle for oil rights. But he knows there's more, and soon his obsession with her threatens to derail his plans... To save her family's ranch, Chelsea is tempted to snare Nolan in a seduction scheme of her own. But when attraction takes over, will her family loyalties fall by the wayside?"--Back cover.